Strategic Digital Marketing in F&B Startupreneur Using the AISAS Model - Nugroho Prihantoni Wibowo; Adam Faturahman; Muhamad Yusup; Nuke Puji Lestari Santoso; Abdullah Arif Kamal (Pandawan Incorporation, Alphabet Incubator Universitas Raharja, 2026)
This research is motivated by the phenomenon of accelerated development of digital technology that has fundamentally transformed consumer behavior and the competitive landscape of marketing strategies in the Food and Beverage (F&B) industry, especially in the rice bowl startup business model that has a very high dependence on the digital platform ecosystem. The purpose of this study is to analyze in depth the influence of digital marketing strategies through the AISAS (Attention, Interest, Search, Action, Share) model framework on consumer purchasing decisions in the digital era. The method used is an explanatory quantitative approach by collecting data through distributing questionnaires to 133 respondents who have experience consuming rice bowl products, then analyzed using the Partial Least Squares Structural Equation Modeling (PLS- SEM) technique through Smart PLS software. The results of the study revealed that the AISAS model has a very significant and strong influence on purchasing decisions with an R² value of 0.978, which means that 97.8% of the variation in purchasing decisions can be accurately explained by these variables. Partially, the Attention variable emerged as the most dominant factor, followed by Interest and Search, while the Share variable showed a negative relationship of -0.169, indicating that content sharing behavior does not automatically drive an increase in direct purchasing decisions. In conclusion, strengthening visual appeal and easy access to information are the main keys to marketing success, although social engagement or experience sharing strategies still require in-depth evaluation to improve their effectiveness.